Decadal trends and regional disparities in tuberculosis burden: a comprehensive analysis of global, African, and Southeast Asian data from the GBD 1990–2021 - Xie, Shiwei; Xiao, Heng; Xu, Lei; Zhang, Fan; Luo, Mingwei (Frontiers in Public Health, 2025)
BackgroundTuberculosis (TB), an infectious disease caused by Mycobacterium tuberculosis, remains a major global public health challenge, particularly in developing countries. Despite a global reduction in TB incidence from 2015 to 2020, the disease continues to be prevalent, with 9.4 million new cases and 1.35 million deaths reported in 2021. This study aims to assess the global, regional, and national burden of TB, with a specific focus on Africa and Southeast Asia, using data from the Global Burden of Disease Study.MethodsData from the Global Burden of Disease 2021 (GBD 2021) study were used to evaluate TB incidence, prevalence, mortality, and disability-adjusted life years (DALYs) from 1990 to 2021. Statistical analyses were conducted using R software and Joinpoint Regression Program to identify trends in age-standardized incidence rate (ASIR), age-standardized mortality rate (ASMR), and age-standardized DALY rate (ASDR). The annual percentage change (APC) was calculated to assess the significance of temporal trends.ResultsFrom 1990 to 2021, global age-standardized rates of TB declined markedly, with ASIR decreasing from 173.0 to 103.0 per 100,000, ASMR from 40.0 to 14.0, and ASDR from 1,650.6 to 580.3. Although incident case numbers slightly declined globally, absolute numbers increased in Africa and Southeast Asia, despite reductions in standardized rates. The disease burden has shifted from younger to older age groups, reflecting population aging. Males consistently exhibited a higher burden than females, though sex disparities narrowed over time. Joinpoint regression confirmed sustained declines in all indicators, particularly in Africa and Southeast Asia. Projections to 2040 suggest continued reductions and convergence in burden across regions. Spatial analyses identified persistent high-burden clusters in sub-Saharan Africa and Southeast Asia, despite overall global improvement.ConclusionTB remains a significant public health issue, especially in Africa and Southeast Asia. While global incidence and mortality have decreased, persistent regional disparities call for more targeted interventions. Ongoing global efforts are essential to further reduce TB-related morbidity and mortality.